Issues of medical rehabilitation of patients in vegetative state - Leonid B. Likhterman (LLC "MEDIAFORMAT", 2022)
Organizational and scientific aspects of severe chronic disorders of consciousness were analyzed. Three groups of patients in a persistent vegetative state were distinguished based on the prognosis.